2l+2w=p

Subtract 2w from both sides of the equation.

2l=p-2w

Divide each term in 2l=p-2w by 2.

2l2=p2+-2w2

Cancel the common factor of 2.

Cancel the common factor.

2l2=p2+-2w2

Divide l by 1.

l=p2+-2w2

l=p2+-2w2

Cancel the common factor of -2 and 2.

Factor 2 out of -2w.

l=p2+2(-w)2

Cancel the common factors.

Factor 2 out of 2.

l=p2+2(-w)2(1)

Cancel the common factor.

l=p2+2(-w)2⋅1

Rewrite the expression.

l=p2+-w1

Divide -w by 1.

l=p2-w

l=p2-w

l=p2-w

l=p2-w

Solve for l 2l+2w=p